Fortalecimiento de la identidad y autonomía personal en niños de 4 años con la rutina diaria. - Rosero Barriga, Adriana Francisca (2023)
The present investigation is focused on analyzing the problem in relation to the elements to be developed to strengthen identity and personal autonomy in 4-year-old children during the 2022-2023 school year, in which it was sought to develop basic identity and autonomy skills, with the daily routine in four-year-old children in the Educational Unit "Alejandro Dávalos Calle" belonging to the Salcedo district. This research is important because it will allow parents to use a creative technique to establish habits in children. This research had a qualitative approach to deepen the analysis and interpretation of the educational reality, the deductive method was used because it helped to describe the lack of autonomy in children; at the same time; the use of the bibliographic method was necessary because it facilitated the analysis and synthesis of theories and concepts related to the variables; At the same time, surveys were carried out with the parents and an interview with the teacher, in order to obtain the necessary information for its analysis.